The safety of e-bikes in The Netherlands - Paul Schepers; Karin Klein Wolt; Elliot Fishman (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
This case-control study compares the likelihood and injury severity of crashes between users of e-bikes and classic bikes in The Netherlands. Use of e-bikes with a maximum speed of 25 km/h is rapidly increasing in European countries. Cyclists being hospitalised are compared to those being sent home after the treatment at the emergency department in order to compare the injury consequences between e-bike and classic bike victims. Whilst results suggest that e-bike and classic bike users are equally likely to be involved in a crash and the severity of crashes are also about equal, the overall impact of e-bikes on road safety is complex and requires more research. As with all forms of physical activity, injuries need to be weighed against the health benefits of more cycling.
Keywords: 330